Memory Cafés and Dementia-Friendly Libraries: Management Considerations for Developing Inclusive Library Programs. Issue 3 (2nd April 2020) - Charbonneau, Deborah H.; Rathnam, Priya
Abstract: Memory Cafés bring services to families and individuals experiencing memory loss, mild cognitive impairment, early Alzheimer's, or other dementias. Memory Cafés situated in libraries are designed to be safe, engaging, and welcoming gathering spaces. These equalizing opportunities provide mind-stimulating activities and respond to the growing need to create dementia-friendly library environments. The aim of this article is to highlight management considerations for creating Memory Cafés. Issues such as building community partners, budgeting, planning, library staff training, and marketing are highlighted. Overall, Memory Cafés can be inclusive library spaces for people experiencing different phases of memory loss and their care partners.